2013
DOI: 10.5964/ijpr.v7i2.126
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Couples’ Perceived Similarity at the Initiation Stage and Currently

Abstract: Although prior research (Montoya, Horton, & Kirchner, 2008) has indicated that perceived similarity is more important than actual similarity as a predictor of satisfaction and attraction, there is a lack of research on factors associated with couples' perceptions of similarity in their relationship. In the present study, a sample of couples (both partners) provided ratings of the degree to which they perceived similarity in six areas (background characteristics, attitudes and beliefs, leisure pursuits and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Research has extensively shown that perceiving another person as having more similar attitudes to oneself increases interpersonal attraction . For instance, perceived -and not actual -similarity predicts initial attraction in a speed-dating context (Eastwick et al, 2011;Tidwell et al, 2013), relationship well-being (Klohnen & Mendelsohn, 1998;Sprecher, 2013), and online friendships (Antheunis, Valkenburg, & Peter, 2012).…”
Section: Perceived Similarity As a Trigger Of Uiamentioning
confidence: 99%
See 1 more Smart Citation
“…Research has extensively shown that perceiving another person as having more similar attitudes to oneself increases interpersonal attraction . For instance, perceived -and not actual -similarity predicts initial attraction in a speed-dating context (Eastwick et al, 2011;Tidwell et al, 2013), relationship well-being (Klohnen & Mendelsohn, 1998;Sprecher, 2013), and online friendships (Antheunis, Valkenburg, & Peter, 2012).…”
Section: Perceived Similarity As a Trigger Of Uiamentioning
confidence: 99%
“…Interestingly, recent research suggests that perceiving similarity grows throughout the course of a romantic relationship (Sprecher, 2013) and elicits the sense of belonging to a given group (Easterbrook & Vignoles, 2013). It seems that the UIA phenomenon may have a larger repercussion, not only by facilitating the initiation of interpersonal relationships, but also belonging to social groups.…”
mentioning
confidence: 99%
“…Perceived similarity refers to the degree to which a person believes the other to be similar to himself or herself. It has generally been operationalized by asking participants how similar they are to a target other, who could be an actual friend or a partner (e.g., Sprecher, 2013) or a stranger about whom the participants had just received factual or bogus information (e.g., Hoyle, 1993).…”
Section: Actual Versus Perceived Similaritymentioning
confidence: 99%